The effects of self-efficacy on the use of self-regulated learning strategies and project-based writing performance - Yanping Kong; Chunyan Wang (International Journal of English for Academic Purposes)
This paper explores how the three factors of self-efficacy (SE), namely language self-efficacy, literature search and reading self-efficacy, and research self-efficacy, affect college students’ project-based writing (PBW) process and outcome. We studied 107 college students’ performance on their PBW term papers and their responses to a questionnaire. Structural equation modeling (SEM) was used to analyse the direct and indirect relationships among the latent variables. The findings are as follows: the three factors of SE strongly influence the use of self-regulation strategies (SRS); SE directly predicts writing performance; SE indirectly predicts PBW performance through the mediating effects of cognitive strategies. The more self-efficacious students use self-regulated strategies more frequently and perform better in PBW. Finally, based on the importance of self-efficacy in PBW discovered in the study, the authors suggest that writing strategy scaffolding along with teacher and peer encouragement be provided to improve the students’ self-efficacy in PBW.